Influence of Motivation, Creativity, and Innovation on Food and Beverage Processing Industry Business Perfomance in Pangkalpinang - Rika Rachmawati; Khofifah Habibah Fitria; Wulan Purnama Sari; Reniati Reniati (Publikasi Indonesia, 2022)
This research aimed to determine the effect of motivation, creativity, and innovation on the performance of food and beverage processing industry players in the city of Pangkalpinang. This type of research was quantitative. The population in this study was the food and beverage processing industry players in the city of Pangkalpinang. The sampling technique was carried out by means of Simple Random Sampling and obtained a sample of 133. The data collection techniques used were questionnaires, documentation, and literature studies. The data analysis technique used was a multiple linear analysis technique and used a partial hypothesis test (t) and simultaneously (f) and uses the coefficient of determination. The results of this study are 1) motivation has no effect on the performance of the food and beverage processing industry players in Pangkalpinang 2) creativity has a positive effect on the performance of the food and beverage processing industry players in Pangkalpinang 3) innovation has no effect on the performance of the food and beverage processing industry players in Pangkalpinang 4 ) motivation, creativity, and innovation together have a positive effect on the performance of food and beverage processing industry players.